2017
DOI: 10.1159/000481734
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Aging and Cognitive Dysfunction: Silent Midlife Crisis in the Brain

Abstract: Background: Vascular aging may cause cerebral microvascular damage and cognitive dysfunction. There is incremental evidence that consistently implicates arterial stiffness being involved in the manifestation of cognitive impairment in the elderly. However, few investigations have examined the relationship between arterial stiffness and cognitive impairment in midlife. Summary: Past studies inconsistently showed improved cognitive outcomes after antihypertensive therapy in elderly populations. Nevertheless, rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
(77 reference statements)
0
12
0
Order By: Relevance
“…Adequate blood supply to the brain is crucial, and the brain is sensitive to excessive changes in pressure, ischemia, and flow pulsatility changes that result from vascular aging. One of the main characteristics of vascular aging is arterial stiffness and damage to blood vessels ( Lin et al, 2017 ). Other changes include the decrease in capillary density and the increase in BBB permeability ( Watanabe et al, 2020 ).…”
Section: Vascular Changesmentioning
confidence: 99%
“…Adequate blood supply to the brain is crucial, and the brain is sensitive to excessive changes in pressure, ischemia, and flow pulsatility changes that result from vascular aging. One of the main characteristics of vascular aging is arterial stiffness and damage to blood vessels ( Lin et al, 2017 ). Other changes include the decrease in capillary density and the increase in BBB permeability ( Watanabe et al, 2020 ).…”
Section: Vascular Changesmentioning
confidence: 99%
“…Severe AS is associated with increased arterial stiffness 4,16 . This plays a major role on the cerebral vascular system, and it prompts microvascular ischaemia, structural changes and remodelling, leading to vascular ageing and subsequent cognitive impairment 12,[17][18][19] . Neurocognitive decline in individuals with AS 4,5 further highlights the cardiocerebral linkage.…”
Section: The Cardiocerebral Continuummentioning
confidence: 99%
“…In fact, recent findings have revealed that blood pressure-lowering treatment in young adults might eliminate the progression of the detrimental effects related to arterial stiffness, indicating that younger adults may have more favorable outcomes in cognition than their older counterparts if early intervention is conducted at the subclinical stage. 77 Although there was no impact on risk reduction of probable dementia, a recent trial (SPRINT MIND) showed that among ambulatory adults with hypertension who were treated with a goal of SBP <120 mm Hg, the risk of mild cognitive impairment was significantly reduced, compared to that in those treated with an SBP goal of <140 mm Hg (14.6 vs 18.3 cases per 1000 person-years; HR, 0.81; 95% CI, 0.69-0.95). 78 A recent review of early morning BP surge (EMBS) showed that EMBS was one form of BP variability associated with the occurrence of strokes and other cardiovascular events.…”
Section: B Lood Pre Ssure Control Anti -Hyperten S I On Ag Ents mentioning
confidence: 99%